Migrant educational mismatch and the labour market - Matloob Piracha; Florin Vadean (Institute for the Study of Labor (IZA), 2012)
This paper reviews the literature on educational mismatch of immigrants in the labour market of destination countries. It draws on the theoretical arguments postulated in the labour economics literature and discusses their extension in the analysis of the causes and effects of immigrants' educational mismatch in the destination country. Relevant empirical approaches have been presented which show that immigrants are in general more over-educated than natives and that the reasons for those range from imperfect transferability of human capital to discrimination to perhaps lack of innate ability. It then assesses the state of current literature and proposes an agenda for further research.
urn:nbn:de:101:1-201206147291
Keywords: J24; J61; 330; immigration; education-occupation mismatch; Migranten; Bildungsniveau; Unterbeschäftigung; Humankapital; Matching; Beruf